Development and Effectiveness of UN-MATH Cards in Enhancing Problem-Solving Skills for Elementary School Students - Aprilia, Dian; Nugraheni, Nursiwi (FKIP Universitas Lampung, 2025)
Development and Effectiveness of UN-MATH Cards in Enhancing Problem-Solving Skills for Elementary School Students. Objectives: This research aims to develop a UNO media called UN-MATH (Uno Mathematics), which is used in game-based learning to help fourth-grade students improve their problem-solving skills in addition and subtraction materials. Methods: The type of research used is Research and Development (R&D). The research design applied is the ADDIE design, which consists of five stages: analysis, design, development, implementation, and evaluation. The data collection techniques used in this research consist of test and non-test techniques. Test techniques include pre-test and post-test, while non-test techniques include observation, interviews, questionnaires, and documentation. Findings: Based on the validation results by media experts, content experts, and language experts, the following results were obtained: the assessment from the media expert is 90% (very feasible), the content expert is 93.1% (very feasible), and the language expert is 92.8% (very feasible). The assessment from the three experts indicates that the UN-MATH card media is suitable for use. The data analysis techniques used in this study include normality tests, t-tests, and N-Gain tests. The results of the normality test show that the significance value (Sig.) > 0.05, which means the data is normally distributed. Based on the paired t-test results in the control class, a Sig. (2-tailed) value of 0.000 was obtained, indicating that the average post-test score increased compared to the pre-test score. Next, the N-Gain test results for the control class were 0.5630, which falls into the moderate and fairly effective category. The same thing happened in the experimental class, where the paired t-test results showed a Sig. (2-tailed) value of 0.000, which means the average post-test score increased compared to the pre-test. Additionally, the N-Gain test results for the experimental class were 0.7004, which falls into the moderate and fairly effective category. Conclusion: Thus, based on the results of the data analysis, the UN-MATH card media has proven effective in mathematics learning to enhance problem-solving skills in addition and subtraction materials. Keywords: learning media, un-math cards, problem-solving skills.